The effect of fontanel on scalp EEG potentials in the neonate. Issue 9 (September 2015) - Gargiulo, P.; Belfiore, P.; Friðgeirsson, E.A.; Vanhatalo, S.; Ramon, C.
Highlights Fontanels in the neonatal skull form spatial discontinuity in the head models. EEG simulation of the whole cortex activity discloses no distortion by fontanels. The relative effect of fontanels on scalp EEG potentials is negligible.